Challenges and critical success factors for the conventional banks of Bangladesh - Tabassum Tanny, Mohibba; Islam, Rafikul; Wan Husain, Wan Rohaida (World Academy of Islamic Management (WAIM), 2025)
This paper aims to identify the challenges faced by conventional banks in Bangladesh in providing quality service and to determine the corresponding critical success factors (CSFs) to address these challenges. Semi-structured online interviews were conducted with 14 bankers from conventional banks in Bangladesh, selected using purposive sampling. Most respondents had over 20 years of experience, indicating their maturity and ability to understand the challenges from both macro and microeconomic perspectives. The qualitative analysis of the interview transcripts revealed six key challenges and 35 corresponding CSFs. The challenges include the global financial crisis, lack of effective governance and accountability, liquidity crisis, export-import and remittance issues, insufficient bank technology development, and employees with insufficient banking knowledge. This study focuses exclusively on challenges faced by Bangladeshi private conventional banks, and its findings may not apply to government and Islamic banking sectors. Identifying these challenges and their CSFs can help conventional banks gain a sustainable competitive advantage by effectively allocating resources and enhancing their operational performance.